Degrees of difference : reflections of women of color on graduate school - McKee, Kimberly (Kimberly D.); Delgado, Denise A.; Leong, Karen J., 1968- (University of Illinois Press, 2020)
"Although universities have begun to assert a commitment to diversity and inclusivity, this directive has not translated into actual support for underrepresented communities, especially women of color graduate students. It is still commonplace for these students to encounter sexism, racism, homophobia, and classism among fellow graduate students and faculty-often all at the same time. These women encounter fellow graduate students who look down on community college graduates and faculty who do not support ethnic studies or work on people of color. Male scholars dominate classroom texts, and if there is a female scholar included, she is inevitably white. Students are asked inappropriate and invasive questions as they begin to feel like imposters among a sea of white faces. Degrees of Difference bridges the political and personal gap by providing frank and honest reflections on the power relationships that exist within higher education. Contributors come from across the academy, including social work, medicine, history, and ethnic studies, providing diverse perspectives on navigating the challenging path of graduate school. A Latina reflects on the failure of social work curriculum to fully address racial/ethnic minorities, a queer black feminist shares strategies for navigating med school, and one woman of color gives insight into the added hurdles of raising two children while finishing her dissertation. Because there is a dearth of resources for graduate students of color, especially women, this volume will become a go-to resource for navigating higher education. However, in addition to reaching out to women of color, this collection should also be seen as a tool to educate men of color, white allies, and family members on the experiences of women of color in graduate school"--